Endothelial Progenitor Cell Levels and Extent of Post-prandial Lipemic Response - Akcan, Buket; Örem, Asim; Altinkaynak, Yahya; Kural, Birgül; Örem, Cihan; Sönmez, Mehmet; Serafini, Mauro (Frontiers in Nutrition, 2022)
Due to the frequency of meal ingestion, individuals spend the majority of the day, approximately 18 h, in a status of postprandial (PP) stress. Remnant-like lipoprotein particles (RLPs) are predominant in postprandial phase playing an important role in the development of atherosclerosis. Endothelial progenitor cells (EPCs) have been suggested to play a role in vessel wall homeostasis and in reducing atherosclerosis. However, there is no information about peripheral blood EPCs number following PP stress. We investigated the association between circulating EPCs levels and extent of postprandial lipemia in healthy subjects following a high fat meal. Eighty-four healthy subjects (42 men, 42 women) aged 17-55 y were included in the study. Postprandial lipemic response of subjects were determined by Oral Fat-Loading Test (OFLT). All subjects were classified on the basis of their plasma TG levels after postprandial lipemic stressors in category 1 (low), 2 (moderate) and 3 (high). Circulating EPCs numbers were measured by flow cytometry method. There was a significant difference in terms of lipid parameters between men and women: HDL-C was significantly lower in men than in women . TC LDL-C TG and TG-AUC were significantly higher in men than women. There was no significant difference between the genders in terms of CD34+KDR+ and CD34+KDR+CD133+cell number and MMP-9 levels. VEGF levels were significantly higher in men than women TC, LDL-C, and TG were significantly higher in the 3rd category than 1st and 2nd categories in women. Age, BMI, fat rate, TG, TC, and LDL-C were significantly higher in the 3rd category than 1st category in men. Circulating numbers of EPCs in men were significantly higher in the postprandial hyperlipidemia group than in the low TG levels category, independently from age Circulating EPC levels showed a positive correlation with OFLT response in men Also, OFLT response showed a strong positive correlation with fasting TG levels EPC levels in women’s categories were not different. Increased EPCs levels in subjects with different postprandial hyperlipidemia may be associated with a response to endothelial injury, related to increased atherogenic remnant particles at the postprandial phase.